THE POWER OF FEMALE SEXUALITY IN BASRI AND SALMA IN A NEVER ENDING COMEDY: A FEMINIST SEMIOTIC PERSPECTIVE - Bahrul Amsal; Sunaniah Sunaniah; Ulfa Utami Mappe (Universitas Negeri Makassar, 2026)
The short film Basri and Salma In A Never Ending Comedy is a drama-comedy set in the Bugis-Makassar community. The Bugis-Makassar community adopts a strong patriarchal value that places men as the dominant party in determining the position of women. This film provides an insight into the limitations faced by women in making decisions about whether or not to have children. The film Basri and Salma In A Never Ending Comedy is very interesting because it conveys a message about the power of female sexuality, demonstrating autonomy and control over one's body. This research is a qualitative study that involves the development of concepts based on existing data. The discussion uses a feminist semiotic analysis approach to describe data in the form of signs based on screenshots of scenes from the film Basri and Salma In a Never Ending Comedy, leading to a conclusion. The research findings conclude that the scenes in the film Basri and Salma In A Never Ending Comedy, first, depict the subordinate position of women within the family, as seen in the dinner scene. Secondly, it demonstrates the concept of power referred to as the power of sexuality, which grants women the authority to determine their bodily autonomy.